Falling standard of undergraduate medical education in Pakistan - Iqbal, Tehseen (Pakistan Journal of Physiology, 2019)
Pakistan is not only producing doctors for its people but it is also providing efficient doctors to all parts of the world. Unfortunately, standard of medical education in Pakistan is deteriorating. This is not the story of one day, it has a long history of ignoring this field for many years by many successive governments. Discussed here are some of the reasons and their solutions. Lack of political will of Governments, lack of roper hierarchy to control Medical Education, lethargy of training institutions for Medical Teachers, lacunas in examining bodies and examination system, easy going and short cut seeking behaviour of medical students and their study from substandard medical books are the main reasons. Establishment of an independent Medical Education Commission and medical education hierarchy, improving the medical teachers training, removing lacunas in the examination system, developing the writing skill of students reviving the habit of reading standard books by the students can improve our medical education. Pak J Physiol 2019;15(4):1–2